2016
DOI: 10.31234/osf.io/fkrxd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting Mental Simulation in Language Comprehension: Six Replication Attempts

Abstract: The notion of language comprehension as mental simulation has become popular in cognitive science. We revisit some of the original empirical evidence for this. Specifically, we attempted to replicate the findings from earlier studies that examined the mental simulation of object orientation, shape, and color, respectively, in sentence-picture verification. For each of these sets of findings, we conducted two web-based replication attempts using Amazon's Mechanical Turk. Our results are mixed. Participants resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 12 publications
5
38
0
1
Order By: Relevance
“…Similar findings have been obtained for sentences implying orientation (Stanfield & Zwaan, 2001), visibility (Yaxley & Zwaan, 2007), color (Zwaan & Pecher, 2012), number (Patson, George, & Warren, 2014), and distance (Vukovic & Williams, 2014) of described objects. Zwaan and Pecher (2012) showed that prior findings on the perceptual dimensions shape and orientation obtained with the sentencepicture verification task could be replicated in a more heterogonous population (i.e., not only involving psychology undergraduates) and in a less controlled environment than the laboratory. Together, the aforementioned studies indicate that the match effect is robust and replicable.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings have been obtained for sentences implying orientation (Stanfield & Zwaan, 2001), visibility (Yaxley & Zwaan, 2007), color (Zwaan & Pecher, 2012), number (Patson, George, & Warren, 2014), and distance (Vukovic & Williams, 2014) of described objects. Zwaan and Pecher (2012) showed that prior findings on the perceptual dimensions shape and orientation obtained with the sentencepicture verification task could be replicated in a more heterogonous population (i.e., not only involving psychology undergraduates) and in a less controlled environment than the laboratory. Together, the aforementioned studies indicate that the match effect is robust and replicable.…”
Section: Introductionsupporting
confidence: 84%
“…Participants pressed the space bar if they had understood the sentence, and then a centrally presented fixation cross appeared for 500 ms (cf. Zwaan & Pecher, 2012), followed by a picture. Participants pressed the "j" key for "yes" responses and the "f" key for "no" responses.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies that could be considered as pushing for unified accounts have become positioned in the debate. For instance, Barsalou () has often been considered favoring an embodied cognition account (e.g., Zwaan & Pecher, ), but should be read as a unified account.
The way I see it, three basic approaches to knowledge exist in modern cognitive science and neuroscience: (a) classic representational approaches based on amodal symbols, (b) statistical and dynamical approaches such as connectionism and neural nets, and (c) embodied approaches such as classic empiricism, cognitive linguistics, and situated action. […]What I have tried to do in formulating perceptual symbol systems is to integrate the positive contributions of all three approaches.
…”
Section: Not So Symbolic and Not So Embodied Accounts Of Cognitionmentioning
confidence: 99%
“…For example, after reading a sentence like The ranger saw the eagle in the sky, participants are faster to recognise a picture of an eagle with extended wings than with folded wings, suggesting that reading the sentence resulted in a perceptual representation of an eagle in flight (Zwaan, Stanfield, & Yaxley, 2002; see also Kaschak et al, 2005;Kaup, Yaxley, Madden, Zwaan, & Lüdtke, 2007;Solomon & Barsalou, 2004;Vandeberg, Eerland, & Zwaan, 2012;Zwaan & Pecher, 2012;Zwaan & Yaxley, 2004). Recent research also suggests that prior exposure to an object in a particular orientation which mismatches with the orientation implied in a subsequently presented sentence can produce disruption to reading as evidenced in both eye-tracking (Wassenburg & Zwaan, 2010) and event-related brain potentials (Coppens, Gootjes, & Zwaan, 2012).…”
Section: Introductionmentioning
confidence: 96%